Karakteristik Pelayanan Rasul Paulus Menurut 1 Tesalonika 2:1-12 Dan Penerapannya Bagi Hamba Tuhan Masa Kini - Yulianus Latuihamallo; Debbie Y. Refialy; Masye Rompa; Vemi Baware (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2021)
This article discucces about the characteristics that servant of God should have in their involvement in order to serving God by imitating the life of the Apostle Paul. Some of the characteristics of the Apostle Paul’s ministry that can be applied, that are Pure in his motivation, ready to take risks, Pleasing to God, Friendly, independent, live in holiness, faithful in his ministry, have clear message content. The purpose of this research is to find out how to apply the characteristics of the ministry of the Apostle Paul according to 1 Thessalonians 2:1-12. The approach of this article is carried out with a literature study through various books and articles that are related to the topics discussed. As the conclusion of this article are first, the characteristics of the ministry that the Apostle Paul has based on the call of the Gospel have become imprint, root and nature in his life so that even though many dangers he has faced but he could overcome it,also have an impact on the spiritual growth of the congregation he serves so that the congregation grows in their faith, hope and love in Christ